PENYELESAIAN SENGKETA TANAH DESA KOTO TUO KECAMATAN XII KOTO KAMPAR ANTARA KELOMPOK TANI OSANG JAYA DENGAN PT. SUMATERA AGRO TUNAS - Teguh Risyan Putra; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Land has a very close relationship with humans. The importance of the meaning of land for human life is because human life cannot be separated from the soil at all. The phenomenon of ulayat land disputes coming to the surface is largely the result of land acquisition for development purposes. One of the land dispute cases is the ulayat land dispute between the residents of the village of Koto Tuo, sub-district XIII, Koto Kampar and PT. Sumatra Agro Tunas.This type of research can be classified in the type of sociological law research (empirical), because in this study the author directly conducts research on the location or place under study in order to provide a complete and clear picture of the problem being studied. This research was conducted in the village of Koto Tuo, District XIII, Koto Kampar, which aims to find out how the implementation of the peace agreement between the Osang Jati farmer group and PT. Sumatra Agro Tunas while the population and sample are the Village Head of Koto Tuo, District XIII Koto Kampar, Ninik Mamak, District XIII Koto Kampar, Director of PT. Sumatra Agro Tunas and Head of the Osang Jaya Farmers Group. Sources of data used are primary data, and secondary data. Data collection techniques in this study were interviews, and literature review.The conclusions that can be obtained from the results of the study are First, Settlement of customary land disputes in the village of Koto Tuo, XIII district of Koto Kampar between the Osang Jati farmer group and PT. Sumatra Agro Tunas did not run well. PT. Sumatra Agro Tunas is not subject to the agreed points of agreement and does not carry out the agreed obligations. Second, the obstacle to resolving the customary land dispute in the village of Koto Tuo, District XIII, Koto Kampar, between the Osang Jati farmer group and PT. Sumatra Agro Tunas, among others, consists of not implementing the results of the agreement by PT. Sumatra Agro Tunas, Lack of authority of the Kampar district government and the lack of details on the position of the parties and Third, Efforts made in resolving ulayat land disputes in the village of Koto Tuo, subdistrict XIII, Koto Kampar, between the Osang Jati farmer group and PT. Sumatera Agro Tunas, among others, the Kampar district government, has mediated in resolving the conflict between the residents of Koto Tuo Village, XIII Koto Kampar District and PT. Sumatra Agro Tunas.Keywords: Settlement, Dispute, Communal Land